Response of Paid Student Subjects to Differential Behaviour of Robots in Bifurcated Duopoly Games - Hoggatt, A. C. (Review of Economic Studies, 1969)
Journal Article Response of Paid Student Subjects to Differential Behaviour of Robots in Bifurcated Duopoly Games Get access A. C. Hoggatt A. C. Hoggatt University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 4, October 1969, Pages 417–432, https://doi.org/10.2307/2296468 Published: 01 October 1969 Article history Received: 15 February 1969 Revision received: 15 May 1969 Published: 01 October 1969